The Association between Maternal Body Mass Index and the Risk of Perinatal Depression - de los Reyes, Samantha; Dude, Annie; Adams, Marci; Castille, Deshala; Ouyang, David W.; Plunkett, Beth A. (American Journal of Perinatology, 2021)
Objective The aim of this study was to evaluate whether the risk of perinatal depression is associated with body mass index (BMI) category.Study Design We performed a retrospective cohort study of women who completed an Edinburgh Postnatal Depression Scale (EPDS) questionnaire during the antepartum period at an integrated health system from January 2003 to May 2018. Risk of perinatal depression was defined as a score of ≥10 on the EPDS or an affirmative response to thoughts of self-harm. Risk of perinatal depression was compared by first trimester BMI category, defined as underweight (BMI: <18.5 kg/m2), normal weight (BMI: 18.5–24.9 kg/m2), overweight (BMI: 25.0–29.9 kg/m2), or obese (BMI: ≥30.0 kg/m2). Univariable analyses were performed using χ2, Fisher's exact test, analysis of variance, Kruskal–Wallis, and Wilcoxon rank-sum tests as appropriate to evaluate the association between maternal BMI category, demographic and clinical characteristics, and risk of perinatal depression. Logistic multivariable regression models were performed to adjust for potential confounders identified as variables with p < 0.10 in univariable analysis.Results Our analysis included 3,420 obese women, 3,839 overweight women, 5,949 normal weight women, and 1,203 underweight women. The overall median gestational age at EPDS administration was 27 weeks (interquartile range: 23–29). Overweight and obese women were more likely to be non-Hispanic Black, Hispanic, multiparous, to have public insurance, prepregnancy diabetes, and chronic hypertension as compared with normal or underweight women (p < 0.001). In univariable analysis, the risk of perinatal depression was not significantly different among underweight (10.8%, odds ratio [OR]: 0.86, 95% confidence interval [CI]: 0.79–1.18) or overweight women (12%, OR: 0.96, 95% CI: 0.79–1.18); however, the risk was higher among obese women (14.7%, 95% CI: 1.21–1.55) compared with normal weight women (11.2%). In multivariable analysis, obesity remained associated with an increased risk of perinatal depression (adjusted OR: 1.19, 95% CI: 1.04–1.35).Conclusion Obesity is associated with an increased risk of perinatal depression as compared with women of normal weight.Key Points
Keywords: obesity; EPDS; Edinburgh Postnatal Depression Scale; self-harm; perinatal depression